Intolerance in the Fatwa on the Prohibition of Interfaith Greetings: Its Impact on Islamic Family Law and Social Harmony - Rahman, Encep Taufik; Dunur'aeni, M. A. E.; Suganda, Ahmad; Ahyani, Hisam; Rozikin, Opik (Hikmatuna : Journal for Integrative Islamic Studies, 2024)
The fatwa on the prohibition of inter-religious greetings issued by the Majelis Ulama Indonesia (MUI) in English Indonesian Theologian Council has caused controversy in the context of inter-religious relations in Indonesia. This study aims to evaluate the impact of the fatwa on Islamic family law and social harmony, focusing on the intolerance caused by interfaith interactions. Using a qualitative approach, this study conducted a content analysis of the text of the Indonesian Theologian Council fatwa and literature related to maqashid al-syariah and Islamic family law. Data were obtained through a documentation study of Indonesian Theologian Council fatwas, books, articles, and academic publications. The analysis technique involved identifying the main themes in the fatwa, comparing them with maqashid al-syariah principles, and evaluating their impact on multicultural family relationships and social harmony. The results show that this fatwa, although aimed at protecting Islamic identity, has the potential to cause tension in family relationships that have members with different religious backgrounds and undermine social harmony. The research emphasizes the need for open dialogue between scholars, academics and the community to find a more inclusive and tolerant solution. A more moderate approach is hoped to be adopted to create interfaith harmony and maintain harmony in Indonesia's multicultural society.